(untitled) (World Bulletin of Public Health, 2022)
The results of a study of 130 patients with purulent soft tissue diseases on an outpatient basis were studied. Depending on the method of treatment, all observed patients were divided into two groups: I the group included 62 patients with purulent diseases of soft tissues who, as a local treatment, used wound sanitation with a 25% solution of dimethyl sulfoccide with the imposition of levomekol ointment under a gauze bandage. The main group II patients received surgical treatment of a purulent focus, sanitation and application of the wound with an electroactivated solution, Electroactivated solution Anolyte and Electro-activated solution Catholyte. The research results showed that physicochemical methods of treating patients with the use of a 25% solution of dimeccide and Electroactivated solution Anolyte and Electro-activated solution Catholyte is an effective, simple and convenient way to treat purulent soft tissue diseases on an outpatient basis